Nivel de estrés académico en estudiantes de pregrado de la facultad de Psicología de la Universidad Antonio Nariño - Bogotá, sede sur (2023)
The purpose of the current study was to analyze the level of academic stress in undergraduate students of the Faculty of Psychology of the Antonio Nariño University, south campus, Bogotá. In this way, different specific objectives are articulated; in the first instance, identify the stressors, symptoms and coping strategies; Secondly, to contrast the levels of academic stress in students of the distance and face-to-face modality in the Faculty of Psychology and, finally, to show the difference in the levels of academic stress in relation to the sex and occupation of the students of the Faculty. of psychology.